PIHPS PRICE MONITORING RESULTS MANUFACTURER PRICES - Muammar Khaddafi; Chalirafi; Munandar; Mohd Heikal; Rico Nur Ilham (RADJA PUBLIKA, 2023)
The objective to be achieved in this research is to support Bank Indonesia (BI) in updating data from the Strategic Food Price Information Center (PIHPS), which is an information center that contains prices of 7 strategic food commodities with the aim of price monitoring, policy coordination and means to expand access to information. for society. The methods used in this research are community empowerment methods, program implementation methods and activity roadmaps targeting producers, namely companies/industry/agricultural farmer households/farmer group associations that produce goods. In general, the methodology for enumerating price data is carried out by conducting direct interviews with respondents every month.